Socio-Scientific Issue Application in the PBL Model: Is that Effective in Improving Chemical Literacy? - Putri, Az-zahra Jasmine Heru; Susilowati, Endang; Mulyani, Sri (Jurnal Inovasi Pendidikan IPA, 2025)
Science education, especially chemistry, emphasizes the application of science to solve problems encountered in daily life to foster chemical literacy skills. This study aims to prove the impact of socio-scientific issue (SSI) application in the problem-based learning (PBL) model on student’s chemical literacy ability on acid and base materials. This study employed a quasi-experimental method through a pretest-posttest nonequivalent control group design. Its population consisted of 11th-grade science students from one of Surakarta’s public high schools in the 2023/2024 academic year. It used class XI.6 as the control class and class XI.7 as the experimental class. The sample was established using the cluster random sampling technique. Based on the analysis of the hypothesis test carried out with the independent sample t-test, the Sig. value is 0.000. The mean chemical literacy score in the experimental class is 72, whereas that in the control class is 62. The enhancement of chemical literacy in the experimental class is 63% (quite effective), while that in the control class is 50% (less effective). This proves that the effect of SSI application in the PBL Model on students’ chemistry literacy ability was more significant than the PBL without SSI application